A carbon-capped supply chain network problem - Diabat, A.; Simchi-Levi, D. (2009 IEEE International Conference on Industrial Engineering and Engineering Management, 2009)
The Kyoto protocol was negotiated as a global effort to reduce greenhouse gas (GHG) emissions. The future standing of companies will be seriously affected by the steps they take today in regards to the environment. Perhaps, if vigilant actions are not taken by a firm then it could easily be left behind in today's highly competitive world. This paper presents a novel optimization model for green supply chain management, which integrates environmental management and its impact into the supply chain while taking carbon emissions into account. The model, which we formulate as a mixed-integer program (MIP), can help to reveal an optimal strategy for companies to meet their carbon cap, while minimizing opportunity cost. We demonstrate the viability of the model via a computational study.